2013
DOI: 10.1007/s10884-013-9314-5
|View full text |Cite|
|
Sign up to set email alerts
|

Integrable Systems of Neumann Type

Abstract: We construct families of integrable systems that interpolate between N -dimensional harmonic oscillators and Neumann systems. This is achieved by studying a family of integrable systems generated by the Casimir functions of the Lie algebra of real skew-symmetric matrices and a certain deformation thereof. Involution is proved directly, since the standard involution theorems do not apply to these families. It is also shown that the integrals are independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Those brackets were also used to analyze Clebsh and Neumann systems in [3]. We recommend the articles [5][6][7], where the bracket (2) or some of its modification were used to consider some integrable systems.…”
Section: Introductionmentioning
confidence: 99%
“…Those brackets were also used to analyze Clebsh and Neumann systems in [3]. We recommend the articles [5][6][7], where the bracket (2) or some of its modification were used to consider some integrable systems.…”
Section: Introductionmentioning
confidence: 99%
“…. = a n−1 = 1, we obtain Lie algebra e(n − 1) of Euclidean group with Lie bracket given as a commutator modified by a matrix S. More examples of integrable systems related to Lie algebra A a 1 ,...,a n−1 with standard commutator were considered in [DO12,DR13,DO14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the case α = 0 was considered in [6] we will not discuss it here. The bi-Hamiltonian systems given by the Lie-Poisson bracket {·, ·} 1,α and the constant Lie-Poisson bracket were studied in [7]. By Magri method [12] it can be shown that Casimir functions of the Poisson bracket {·, ·} ,α :…”
Section: Introductionmentioning
confidence: 99%